2021
DOI: 10.7498/aps.70.20201375
|View full text |Cite
|
Sign up to set email alerts
|

Lower turning point convegence zone in deep water with an incomplete channel

Abstract: In a deep sea sound channel, rays will bend due to the sound speed profile, and convergence zone will occur when the rays are intensive. Transmission loss in the convergence zone is smaller and it is conducive to acoustic detection and communication. Therefore the study of acoustic characteristics in convergence zone is always the focus of deep-sea acoustics. A long-range sound propagation experiment is conducted in the South China Sea. An equivalent broadband explosive sound source of 1 kg is placed at a dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Zhang et al [18] analyzed the impact of mesoscale vortices on the convergence zone through the parabolic equation method, determining that warm vortices increase the distance of the convergence zone, while cold vortices make it smaller. Piao et al [19] found that there is a convergence zone in the deep sea at large receiving depths and analyzed the position of the convergence zone using ray mode theory. Wu et al [20] found that, under the influence of the Indian Ocean Dipole, the thermocline fluctuation at the location of the second convergence zone has an important influence on the formation and location of the third convergence zone.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [18] analyzed the impact of mesoscale vortices on the convergence zone through the parabolic equation method, determining that warm vortices increase the distance of the convergence zone, while cold vortices make it smaller. Piao et al [19] found that there is a convergence zone in the deep sea at large receiving depths and analyzed the position of the convergence zone using ray mode theory. Wu et al [20] found that, under the influence of the Indian Ocean Dipole, the thermocline fluctuation at the location of the second convergence zone has an important influence on the formation and location of the third convergence zone.…”
Section: Introductionmentioning
confidence: 99%